4-{[4-(Dimethylamino)benzylidene]amino}-1,5-dimethyl-2-phenyl-1H-pyr azol-3(2H)-one - Asiri, A.M.; Khan, S.A.; Tan, K.W.; Ng, S.W. (International Union of Crystallography, 2010)
The azomethine double-bond in the title Schiff base, C(20)H(22)N(4)O, has an E-configuration. The aromatic ring of the benzylidene portion (r.m.s. deviation 0.011 angstrom) and the five-membered pyrazolyl ring (r.m.s. deviation 0.033 angstrom) form a dihedral angle of 19.0 (1)degrees. The phenyl substituent is twisted by 55.0 (1)degrees with respect to the five-membered ring.